Building a cloud-based data sharing model for the Saudi national registry for implantable medical devices: Results of a readiness assessment. (October 2018) - Alshagathrh, Fahad; Khan, Samina A.; Alothmany, Nazeeh; Al-Rawashdeh, Nedal; Househ, Mowafa
Highlights: Reporting the readiness of hospitals in Saudi Arabia in implementing a national Implantable Medical Device Registry (IMDR). Comparing IMDR implementation readiness for five tertiary hospitals in Saudi Arabia. Recommendations for future plans and research in the development of the IMDR in Saudi Arabia. Abstract: Background: Implantable medical device registries are used as a medium to conduct post-marketing surveillance. Little information is available on the development and implementation of implantable biomedical device registries in general and specifically in Saudi Arabia and the Middle East. Objectives: This study presents the experiences of building an implantable medical device registry in the Kingdom of Saudi Arabia. The work specifically addresses the early experiences of the Saudi Food and Drug Authority in the planning and development of a data sharing model for the implementation of a medical device registry at different hospital sites within the country. Methods: A two-year case study in which 60 health professionals from 5 hospitals in Saudi Arabia participated in a readiness assessment survey. The readiness assessment examined system-level capacity, hospital workflow and operations, clinical staff-level engagement, and technological assessment as they relate to the implementation of the Implantable Medical Device Registry (IMDR). Both subjective and objective data were collected as part of the readiness assessment survey at each hospital site. Data was collected from participants either individually or as part of a group at each hospital site. Using Microsoft Excel, Microsoft Word, flip charts, and back-and-forth discussion, the data was descriptively summarized and synthesized to provide an overview of hospital readiness for IMDR implementation. Results: Results show that there are large differences among Saudi hospitals in terms of their readiness for IMDR implementation due to a variety of factors relating to differences in hospital-wide organizational systems, clinical practice, technological infrastructure, and data sharing capabilities. Each of the hospitals surveyed in this study had differences in how clinical biomedical implantation policies and procedures were utilized. Manual entry into the cloud-based IMDR was recommended as the most optimal data sharing model that would mitigate the differences between hospital readiness for IMDR implementation. Conclusion: Registries play a major role in monitoring the effectiveness of implantable biomedical devices. National standardized policies, enforced regulations, and information technology infrastructure are needed to achieve this goal. Furthermore, due to differences in hospital readiness, building a cloud-based registry system through manual data entry into the IMDR was found to be the most appropriate data sharing model that can be implemented at the national level.